How to read the American West : a field guide - Wyckoff, William (Weyerhaeuser environmental book., 2014)
From deserts to ghost towns, from national forests to California bungalows, many of the features of the western American landscape are well known to residents and travelers alike. But in How to Read the American West, William Wyckoff introduces readers anew to these familiar landscapes. A geographer and an accomplished photographer, Wyckoff offers a fresh perspective on the natural and human history of the American West and encourages readers to discover that history has shaped the places where people live, work, and visit. This innovative field guide includes stories, photographs, maps, and diagrams on a hundred landscape features across the American West. Features are grouped according to type, such as natural landscapes, farms and ranches, places of special cultural identity, and cities and suburbs. Unlike the geographic organization of a traditional guidebook, Wyckoff's field guide draws attention to the connections and the differences between and among places.